ETIKA BISNIS ISLAM DALAM FIQIH MUAMALAH DAN IMPLEMENTASINYA DI ERA DIGITAL - Siti Maryam Nst; Roma Rizkina Fatimah Pulungan; Safitri Hasibuan; Fatmah Taufik Hidayat (Jurnal Riset Multidisiplin Edukasi, 2026)
Islamic business ethics is a set of moral values derived from the Qur'an and Hadith that regulate human economic activities. In the framework of fiqh muamalah, business ethics serves as a guideline to ensure that transactions are conducted in accordance with the principles of justice, honesty, and mutual benefit. The rapid development of the digital era has introduced new challenges, including the complexity of online transactions, the potential for fraud, and technology-based financial systems. This study aims to analyze the concept of Islamic business ethics within fiqh muamalah and its implementation in the digital era using a qualitative normative approach through library research. The findings indicate that principles such as honesty (ṣidq), trustworthiness (amanah), justice ('adl), transparency, and the prohibition of riba, gharar, and tadlis remain highly relevant and must be upheld in digital business practices. The implementation of Islamic business ethics in the digital era is essential to create a fair, secure, and sustainable economic system.